2010
DOI: 10.1158/0008-5472.can-09-3289
|View full text |Cite
|
Sign up to set email alerts
|

A MicroRNA Expression Signature for Cervical Cancer Prognosis

Abstract: Invasive cervical cancer is a leading cause of cancer death in women worldwide, resulting in about 300,000 deaths each year. The clinical outcomes of cervical cancer vary significantly and are difficult to predict. Thus, a method to reliably predict disease outcome would be important for individualized therapy by identifying patients with high risk of treatment failures before therapy. In this study, we have identified a microRNA (miRNA)-based signature for the prediction of cervical cancer survival. miRNAs ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
235
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(247 citation statements)
references
References 33 publications
9
235
0
3
Order By: Relevance
“…So we chose cervical squamous cell carcinoma to verify relationship between aberrant expression of miR-203 and cervical tumorigenesis. Our investigation showed miR-203 was down-regulated in sample group in comparison to control group that low expression of miR-203 was correlated with LNM, this is exactly the same result as Hu proved in their study (Hu et al, 2010). miRNA-20a was known to belong to the miR-17-92 cluster, which is the most extensively studied cluster that has an oncogenic function.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…So we chose cervical squamous cell carcinoma to verify relationship between aberrant expression of miR-203 and cervical tumorigenesis. Our investigation showed miR-203 was down-regulated in sample group in comparison to control group that low expression of miR-203 was correlated with LNM, this is exactly the same result as Hu proved in their study (Hu et al, 2010). miRNA-20a was known to belong to the miR-17-92 cluster, which is the most extensively studied cluster that has an oncogenic function.…”
Section: Discussionsupporting
confidence: 86%
“…There is a hypothesis that deregulated synthesis of miRNAs, which in turn regulate protein synthesis, is one of the most important factors contributing to cancer development (Lin et al, 2012;Ma et al, 2012;Liang et al, 2013). Altered miRNA expression profiles have also been reported in cervical cancer as compared with normal cervix (Lee et al, 2008;Hu et al, 2010). miRNAs are different in diverse tumors, research on miRNAs expression profile will contribute to the classification of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also demonstrated that miR-126 has roles in regulating adhesion molecule expression (Harris et al, 2008), providing additional control of vascular inflammation (Harris et al, 2008), regulating the VEGF/PI3K/AKT signaling pathway (Hu et al, 2010), regulating the translation and invasiveness of vascular endothelial cell sprouting (Musiyenko et al, 2008), and governing the integrity and angiogenesis of the vasculature (Kuhnert et al, 2008;Wang et al, 2008b). Using MTT assays, our research showed that the SR of Siha-miR-126 mimic was significantly reduced compared to that of control cells and that the differences between the 2 cell groups increased over time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that microRNAs (miRNAs) act as crucial modulators in cancer progression by targeting mRNAs through cleavage or transcriptional repression (Bartel, 2004). Various miRNAs have been shown to exhibit differential expression between cervical cancer and normal cervical tissues (Wang et al, 2008), and several reports have demonstrated the roles of miRNAs in the proliferation (Yang et al, 2009), apoptosis (Li et al, 2011), and prognosis (Hu et al, 2010) of cervical cancer. However, the role of miRNAs in mediating sensitivity of cells to chemotherapeutic drugs has not been explored in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The recent revelation that miRNAs activity is modulated by phosphorylation (7) should be taken in consideration when designing diagnostic and therapeutic methodologies for more secure and effective methodologies. MiRNAs have been extensively reported to be implicated in the process of drug and radiation resistance, being both miRNA under or over expression important determinants of clinical response after cancer therapy (59)(60)(61)(62). For example, Pedroza-Torres et al, 2016 (63) identified 101 miRNAs that showed significant differences between nonresponders and complete pathological responders.…”
mentioning
confidence: 99%